Cross-triggered and cascaded recycling amplification for ultrasensitive electrochemical sensing of the mutant human p53 gene. Issue 56 (22nd June 2016) - Yang, Cuiyun; Dou, Baoting; Yang, Jianmei; Yuan, Ruo; Xiang, Yun
Abstract : Cross-triggered and cascaded recycling amplification enables the highly sensitive electrochemical detection of the mutant p53 gene in human serum. Abstract : Based on an endonuclease-assisted, cross-triggered and cascaded recycling amplification strategy, the construction of a simple electrochemical sensing platform for the ultrasensitive detection of the mutant p53 gene in human serum is described. Using this new signal amplification approach, the sub-femtomolar level of the mutant p53 gene can be selectively detected.